Metric for strategy implementation: measuring and monitoring the performance - Okfalisa, Okfalisa (Institute of Electrical and Electronics Engineers, 2009)
The strategy formulation in organizations will be useless unless it is well implemented. Measuring and monitoring the performance of strategy implementation are one way solution to identify the success achievement of organizational objectives. To measure and monitor the implementation process based on document analysis and annual report are not enough anymore. Therefore, this paper studies the performance of strategy implementation by investigating the exploration of tangible and intangible knowledge within the organization. The stakeholders' knowledge process while making the quality of decision making is discussed. The complexity of problems and knowledge, the dynamic changes and the environment uncertainty in decision making will be considered as indicators in knowledge management metrics development. To identify the knowledge process in strategy implementation, case study is conducted at Universiti Teknologi Malaysia (UTM). From these interviews, the conceptual metrics are developed. Hence, the strategy implementation can be measured and monitored.